Organochlorine pesticides and polychlorinated biphenyls from a greenhouse area on the Mediterranean coast of Turkey: Distribution, air-soil exchange, enantiomeric signature, and source implications - Can-Guven, Emine; Gedik, Kadir; Kurt Karakuş, Perihan Binnur (Dokuz Eylül Üniversitesi, 2021)
Levels, seasonal variation, and air-soil exchange of 22 organochlorine pesticides (OCPs) and 15 polychlorinated biphenyls (PCBs) were determined in addition to the first insight into the enantiomeric signatures of chiral OCPs in an agricultural region of Turkey. A total of 47 polyurethane foam disk passive air samples and 34 surface/indepth soil samples were analyzed. Sigma OCP and Sigma PCB levels in air samples were 32.6-741 pg/m(3) and nd-2764 pg/m(3), while they were nd-28.1 ng/g dw and nd-0.302 ng/g dw in soil samples, respectively. Dichlorodiphenyl-trichloroethane (DDT) and its metabolites and endosulfan isomers were the most prevalent chemicals along with the light-weighted PCB congeners. During this study, lower or similar contamination levels were observed compared to global studies conducted in agricultural regions. The enantiomer fractions of o,p'-DDT in air samples might be due to re-volatilization of equally depleted enantiomers or fresh input of racemic o,p'-DDT to the air. The fugacity fractions showed that net deposition is the dominant mechanism.
Keywords: Agriculture; Chiral; Fugacity; Passive air samplers; Persistent organic pollutants